A panoptic view of the Taurus molecular cloud: I. The cloud dynamics revealed by gas emission and 3D dust - Soler, Juan D.; Zucker, C.; Peek, J. E. G.; Heyer, M.; Goldsmith, P. F.; Glover, Simon; Molinari, S.; Klessen, Ralf S.; Hennebelle, P.; Testi, L.; Colman, T.; Benedettini, M.; et al. (Astronomy and astrophysics, 2023)
We present a study of the three-dimensional (3D) distribution of interstellar dust derived from stellar extinction observations toward the Taurus molecular cloud (MC) and its relation with the neutral atomic hydrogen (H I) emission at 21 cm wavelength and the carbon monoxide 12CO and 13CO emission in the J = 1 → 0 transition. We used the histogram of oriented gradients (HOG) method to match the morphology in a 3D reconstruction of the dust density (3D dust) and the distribution of the gas tracers’ emission. The result of the HOG analysis is a map of the relationship between the distances and radial velocities. The HOG comparison between the 3D dust and the H I emission indicates a morphological match at the distance of Taurus but an anticorrelation between the dust density and the H I emission, which uncovers a significant amount of cold H I within the Taurus MC. The HOG study between the 3D dust and 12CO reveals a pattern in radial velocities and distances that is consistent with converging motions of the gas in the Taurus MC, with the near side of the cloud moving at higher velocities and the far side moving at lower velocities. This convergence of flows is likely triggered by the large-scale gas compression caused by the interaction of the Local Bubble and the Per-Tau shell, with Taurus lying at the intersection of the two bubble surfaces.